Diet and the gut microbiome in 10–18-month-old children living in urban slums of Mumbai, India (OR01-08-19) - Huey, Samantha; Rajagopalan, Kripa; Venkatramanan, Sudha; Udipi, Shobha; Thakker, Varsha; Thorat, Aparna; Potdar, Ramesh; Haas, Jere D.; Finkelstein, Julia L.; Knight, Rob; Mehta, Saurabh (Oxford University Press, 2019)
To characterize the gut microbiome and explore associations between dietary intake and gut microbiome composition and predicted function among children at screening for participation in a randomized controlled feeding trial in urban slums of Mumbai, India.